(3JQLeI GdTjN GdOQOjQs
(3ChdgG (B:s
(3JQLeI GdTjN GdOQOjQ , hbO eGJ ai gPg GdSfI CYfj SfI (B1201 (3ef CYjGf GdhbJ TjN GdESdGe CMeO Hf eMeO GdYOhj GdTgjQ HGdOQOjQ s
(3BNQgG (B:s
(3hdeG QLY ef GdML Hfj gPg GdRGhjI HeG Hbi hOaf HgG QMeg Gddg , aEfg de jNda HYOgG eKdg , hGddg CYde s
(3Vef eLehY , JQJjHgG (B: (3ef U (B96 - (3U(B100s
(3hGdTjN GdOQOjQ gh CMeO Hf eMeO Hf CMeO GdYOhj GdeGdcj GdCRgQj GdOQOjQ GdeJhaj SfI (B1201(3g`s
(3hJdj GdJQLeI ELGRGJ ef GdTjN GdOQOjQs
(3hGdTjN eMeO GdOShbjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B108 s
Keywords: (3GdJGQjNs